DEVELOPMENT OF "KERR EFFECT" DEVICES TO MEASURE URINE GLUCOSE LEVELS OF DIABETES MELITUS (DM) PATIENTS - Nayiroh, Nurun; K, Kusairi (Jurnal Neutrino, 2019)
The development of the "Kerr Effect" device has been carried out to measure urine glucose levels of Diabetes Mellitus (DM) patients by applying an external electric field of two parallel plate capacitors. The purpose of this research was to design and construct a new "Kerr Effect" device to measure urine glucose levels of DM patients, to determine the effects of external electric fields and glucose concentrations on light polarization. The measurement of the polarization changes was done by emitting polarized light through a glucose standard solution sample and urine samples of DM patients. In this measurement, the sample was irradiated with an external electric field (0 kV / m - 80 kV / m) of parallel plate capacitors, and the changes of light polarization in the sample were observed. The obtained data of the measurement have been collected and plotted as a graph. The results showed that as the electric field increased the changes in polarization have a tendency to increase. In addition, the amount of glucose concentration in the urine also affected the magnitude of the change in the rotational polarization angle of the light. Therefore, the changes in the rotational polarization angle increase linearly due to the influence of the external electric field and the concentration of glucose in the urine.